2017
DOI: 10.18781/r.mex.fit.1703-9
|View full text |Cite
|
Sign up to set email alerts
|

Situación actual de Colletotrichums spp. en México: Taxonomía, caracterización, patogénesis y control

Abstract: Resumen. Las especies del género

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
(55 reference statements)
1
7
0
9
Order By: Relevance
“…The occurrence of anthracnose not only influences yields, but also affects the quality of the crops. In some cases, the incidence of anthracnose on the fruits has been as high as 100% for pepper, and ranges between 20% and 60% for papaya and physic nut (Rojo‐Báez et al ., ). Annual yield losses can reach 40–80% under favourable conditions, and consequently losses at the pre‐ and post‐harvest stage are considerable.…”
Section: Introductionmentioning
confidence: 97%
“…The occurrence of anthracnose not only influences yields, but also affects the quality of the crops. In some cases, the incidence of anthracnose on the fruits has been as high as 100% for pepper, and ranges between 20% and 60% for papaya and physic nut (Rojo‐Báez et al ., ). Annual yield losses can reach 40–80% under favourable conditions, and consequently losses at the pre‐ and post‐harvest stage are considerable.…”
Section: Introductionmentioning
confidence: 97%
“…There is evidence of a prolonged effect during the greenhouse test of antifungal activity, in which a MIC was identified corresponding to a concentration of 255 µL in 30 capsules and an inhibitory range of 100% for the development of anthracnose by Colletotrichum gloeosporioides during the 12 days after inoculation. Other studies have reported the appearance of the first symptoms of infection up to 51 days after inoculation [ 20 ]. The capsules have demonstrated their extended effect in controlling the release of the remaining inoculum.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados obtenidos coinciden con los trabajos anteriores de Rojo-Baez et al (2017a) y Rojo-Báez et al (2016) quienes en frutos de papaya inoculadas con C. truncatum observaron los primeros sintomas a los tres (ddi) y los acérvulos a los 5 ddi; y en arveja a los 4 ddi. Asimismo, Rojo-Báez et al (2017b) reportan que C. gloeosporioides y C. truncatum poseen amplio rango de hospedantes y que su colonización es intramural subcuticular e intracelular. Estos resultados nos muestran que debemos de implementar diferentes estrategias de manejo de la enfermedad.…”
Section: Prueba De Patogenicidadunclassified